Preparation and characterization of cycloolefin polymer based on dicyclopentadiene (DCPD) and dimethanoocta hydronaphthalene (DMON) - Widyaya, Vania Tanda; Huyen Thanh Vo; Putra, Robertus Dhimas Dhewangga; Hwang, Woon Sung; Ahn, Byoung Sung; Lee, Hyunjoo (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Ring-opening metathesis polymerization (ROMP) and subsequent hydrogenation of the mixture of dicyclopentadiene (DCPD) and 1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene (DMON) were conducted. ROMP was successfully performed at room temperature using WCl6/iBu(3)Al/2-BuOH (1/0.7/1.2) catalyst system when the DCPD/DMON molar ratio was 1. Depending on the DCPD/DMON molar ratio, the catalyst component ratio for the polymerization changed. The double bond in the prepared ROMP polymer could be completely hydrogenated using Ni(acac)(2)/iBu(3)Al at molar ratio of the Ni/double bond in polymer = 0.2 mol% and Al/Ni = 4 when the reaction was conducted at 80 degrees C for 3 h. After hydrogenation, the glass transition temperature (T-g) of all ROMP polymers was decreased by 40 degrees C. Depending on the DCPD and DMON molar ratio, the T-g of the ROMP polymer and hydrogenated ROMP polymer changed. The hydrogenated DCPD-DMON ROMP copolymer was characterized by using 2D H-1-H-1 COSY and 2D H-1-C-13 HSQC NMR spectroscopy. Thermal stability and light transmittance for the ROMP polymer and the hydrogenated ROMP polymer were compared by using TGA and UV. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: OPENING METATHESIS POLYMERIZATION; TUNGSTEN COMPLEXES; ATACTIC POLYMER; TETRACYCLODODECENE; HYDROGENATION